Toxicopathologic Effects of Artemisinin in Broiler Chickens Following a Single Oral Dose: An LD50 Study - Arab, H.A.; Mardjanmehr, S.H.; Shahbazfar, A.; Rassouli, A.; Abdollahi, M.; Nekouie, O. (International Journal of Poultry Science, 2009)
The present study aimed to find LD50 of artemisinin and to characterize the single dose toxicity of the drug following oral exposure. 49 day-old Ross broilers divided into 7 groups; one control, one drug vehicle and five treatment groups. The treatment groups received artemisinin alcoholic solution at doses of 10, 50, 250, 1250 and 2500 mg/kg on day 30 by a crop tube. The control and drug vehicle groups received normal saline and ethyl alcohol, respectively. In the period of study just in 1250 and 2500 mg/kg groups there were a few transient neurological signs like depression and unconsciousness. These signs were also observed in drug vehicle group. None of the birds died, so they were euthanised on day 40. In microscopic examination, only in treatment groups a slight degeneration in liver and kidney as intracytoplasmic eosinophilic inclusions, hepatocellular swelling and bile retention in liver were evident. In brain central chromatolysis, scattered neuronal necrosis, spongy change and focal axonal swelling were observed. It is concluded that artemisinin has a good margin of safety in poultry but in very high doses it may cause some adverse effects.